Desenvolvimento sustentável e agenda de atuação dos bancos públicos comerciais brasileiros: uma análise da estratégia negocial de Desenvolvimento Regional Sustentável (DRS) do Banco do Brasil - Rejani, Fernando Montrezol (2011)
This present paper consists in analyzing the business strategy of Regional Sustainable Development (RSD) of Banco do Brasil (BB) under two aspects, of which, i) aims at identifying if the operations of BB, an hybrid Bank, that is public and private at the same time, have headroom to freely operate as an agent of the Brazilian development; and ii) to verify if the RSD business strategy is consistent with its proposed objectives and if those objectives are being achieved, in line with the perception of the BB employees interviewd in this research. The investigation method uses bibliographical research and the application of primary research with the internal agents of BB, responsible for the performance of the national strategy of RSD. Two types of questionnaires were applied to the target audience. In the first group of interviewed stakeholders (managers in strategic and tactical level), the criteria of data analysis was global. For the second group (managers at operational level), the criteria of data analysis was based on a significant sample of a population of 230 business plans of RSD spreaded throughout the country. What can be concluded in this study is that the operation of BB, as an agent of development of Brazil, it has certain inner limitations due from its own hybrid nature. It is made clear a tension that exists between the traditional commercial operation of the Bank (private nature) and its more social operations (public nature) in the implementation of the national strategy of RSD. It is worth noting that, the development promoted by the RSD has a few gaps, mainly in regards to the environmental component of the sustainable development and also in regards to the difficulty in implementing its methodology towards productive activities in the urban environments. However, it is worth highlighting that the social-environmental presence of BB, with the RSD, enables the social inclusion, by way of access to banking and credit, in a much wider aspect than the Brazilian private banks